Analysis of Factors Associated with the Utilization of Reproductive Health Information Among Adolescents in Siak District in 2024 - Zuliyana, Zuliyana; Fraselia Putri S, Anggia; Elektrina, Oktaliza; Angraini, Vera (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescent reproductive health problems remain a global and national concern, particularly in relation to access to and utilization of reproductive health information. Inadequate utilization of reproductive health information among adolescents may contribute to risky sexual behaviors, early marriage, sexually transmitted infections, and unintended pregnancies. This study aimed to analyze the factors associated with the utilization of reproductive health information among adolescents in Siak District, Siak Regency, Riau Province, in 2024. This study employed an analytic observational design with a cross-sectional approach. The study population consisted of adolescents aged 15–19 years, and samples were selected using proportional random sampling techniques. Data were collected through structured questionnaires and analyzed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate logistic regression analysis. The results indicated that knowledge, attitudes, access to information media, peer support, parental roles, and support from health workers were significantly associated with the utilization of reproductive health information (p < 0.05). Access to information media was identified as the most dominant factor influencing the utilization of reproductive health information among adolescents. Strengthening adolescent-friendly information services, enhancing family support, and implementing digital health literacy interventions are recommended to improve adolescents’ utilization of reproductive health information.